CORRELATED COCHANNNEL LOG-NORMAL INTERFERERS IN CELLULAR RADIO - SAFAK, A; PRASAD, R (Assn Elettrotecnica Ed Elettronica Italiana, 1994)
The probability of co-channel interference (PCI) in cellular radio systems is analyzed assuming that the desired signal and the co-channel interferers are correlated in a log-normal shadowing environment. The correlation between the signals in a log-normal shadowing environment reduces the PCI and hence allows operation with shorter frequency reuse distances and smaller cluster sizes. Compared with omnidirectional systems, the cells employing directional antennas can operate with shorter frequency reuse distances and hence provide better usage of the frequency spectrum.